KESIAPAN IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL - Lilik Suroya; Heru Tjaraka (Jurnal Ekonomi dan Bisnis Airlangga, 2020)
Introduction: This study will identify the readiness to implement the Accrual-Based Government Accounting Standards in the regional public hospital dr. Soedono Madiun.Methods: This research uses a qualitative approach with an explanatory case study method. Implementation of accrual-based Government Accounting Standards must be implemented in 2015 in accordance with the Law of the Republic of Indonesia No. 17 of 2003 concerning State Finance.Results: Human resources in the Finance Department in implementing accrual-based government accounting standards are considered inadequate or inadequate, but the management of RSUD dr. Soedono Madiun strives by disseminating the understanding of accrual accounting, improving formal education, and training so that it has benefits to improve accounting understanding and improve the quality of human resources.Conclusion and suggestion: The main obstacle in the readiness to implement accrual-based Government Accounting Standards is the provincial level legal basis in the form of a Governor Regulation concerning Accrual-based Accounting Policies which underlie Government Regulation No. 71/2010 does not yet exist.